2004
DOI: 10.1038/sj.bjc.6602137
|View full text |Cite
|
Sign up to set email alerts
|

Bax regulates c-Myc-induced mammary tumour apoptosis but not proliferation in MMTV-c-myc transgenic mice

Abstract: The expression of the proto-oncogene c-myc is frequently deregulated, via multiple mechanisms, in human breast cancers. Deregulated expression of c-myc contributes to mammary epithelial cell transformation and is causally involved in mammary tumorigenesis in MMTV-c-myc transgenic mice. c-Myc is known to promote cellular proliferation, apoptosis, genomic instability and tumorigenesis in several distinct tissues, both in vivo and in vitro. Expression of the proapoptotic regulatory gene bax is reduced or absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
(71 reference statements)
3
9
0
Order By: Relevance
“…This is consistent with the established notion that apoptosis is the principal intrinsic mechanism limiting Myc-induced tumorigenesis (24). Recently, however, it was reported that although loss of Bax inhibits apoptosis in a classical, constitutive Myc-transgenic mouse model for mammary tumorigenesis (25), paradoxically such suppression of apoptosis did not appreciably promote Myc-induced tumorigenesis. This inconsistency may indicate that apoptosis suppresses tumorigenesis to different extents in differing tissues.…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with the established notion that apoptosis is the principal intrinsic mechanism limiting Myc-induced tumorigenesis (24). Recently, however, it was reported that although loss of Bax inhibits apoptosis in a classical, constitutive Myc-transgenic mouse model for mammary tumorigenesis (25), paradoxically such suppression of apoptosis did not appreciably promote Myc-induced tumorigenesis. This inconsistency may indicate that apoptosis suppresses tumorigenesis to different extents in differing tissues.…”
Section: Discussionsupporting
confidence: 74%
“…On one hand, Bcl-2 reduces high apoptotic frequency observed in the c-Myc overexpressing mammary glands and accelerates c-Myc driven mammary tumorigenesis 60 but, on the other hand, loss of the pro-apoptotic (and Bcl-2 antagonizing) Bax also reduces apoptosis in the c-Myc induced mammary adenocarcinomas but it does not have any accelerating effect on tumorigenesis. 61 Thus, there are no definitive answers yet to the question whether apoptosis is a major or a minor roadblock hampering c-Myc-driven tumor development in the mammary gland.…”
Section: Mechanisms Of Tumor Suppression By Polarity Genes-cues From mentioning
confidence: 99%
“…For example, in the mouse mammary gland Bax-deficiency suppresses c-Myc-induced apoptosis without having effect on the c-Myc dependent tumorigenesis. 47 Furthermore, there are also tissues like skin keratinocytes, which are not prone to c-Myc-induced apoptosis and in these tissues inhibition of apoptosis may play lesser role in tumor progression. 48 The pro-apoptotic BH3-only member of Bcl-2 family, Bim (Box 2), has also been linked to c-Myc-dependent tumorigenesis.…”
Section: Myc Primes Activation Of the Mitochondrial Pathway Of Apoptosismentioning
confidence: 99%